Thermal fluids at the centre of consumer safety. Issue 12 (December 2016) - Wright, Christopher; Wright, Chris; Anderson, Martin
Abstract : Safety is an important factor when choosing a heat transfer fluid as a heat source for food and drink processing plants. The fluids need to be suitable for incidental contact and not present a significant risk to consumers. This article discusses the importance of the chosen heat transfer fluid in relation to the food supply chain.